An Acoustic Analysis of Student-Produced Speech in Speed Reading Using a Teleprompter at Al Azhar 3 Senior High School Bandar Lampung - Dewi, Hamelia Qomara; Susanto, Susanto; Nanda, Deri Sis (Universitas Pahlawan Tuanku Tambusai, 2026)
This study investigates the acoustic differences in student-produced voice during speed reading with and without a teleprompter in an English as a Foreign Language (EFL) context. The research aims to examine how teleprompter-assisted reading affects fluency, prosody, and pronunciation. A quasi-experimental quantitative design was conducted with 30 senior high school students who were members of the English Club at SMA Al Azhar 3 Bandar Lampung. Each participant performed three reading tasks: without a teleprompter, with a teleprompter at 1% speed, and with a teleprompter at 50% speed. Recordings were analyzed using Praat software to measure pitch, intensity, duration, and pronunciation errors. The findings showed no significant differences in pitch and intensity (p .05). However, reading duration was significantly longer at 1% speed (p .05), indicating more deliberate articulation. Descriptive results also revealed fewer pronunciation errors at 1% speed than at 50% speed. These findings suggest that adjusting teleprompter speed can optimize speech clarity, making teleprompters a valuable tool for improving EFL learners’ fluency and accuracy in public speaking training.